Short-term postoperative outcomes after liver resection in the elderly patient: a nationwide population-based study. Issue 10 (October 2021) - Elfrink, Arthur K.E.; Kok, Niels F.M.; den Dulk, Marcel; Buis, Carlijn I.; Kazemier, Geert; Ijzermans, Jan N.M.; Lam, Hwai-Ding; Hagendoorn, Jeroen; van den Boezem, Peter B.; Ayez, Ninos; Zonderhuis, Babs M.; Lips, Daan J.; et al.
Abstract: Background: Liver resection is high-risk surgery in particular in elderly patients. The aim of this study was to explore postoperative outcomes after liver resection in elderly patients. Methods: In this nationwide study, all patients who underwent liver resection for primary and secondary liver tumours in the Netherlands between 2014 and 2019 were included. Age groups were composed as younger than 70 (70-), between 70 and 80 (septuagenarians), and 80 years or older (octogenarians). Proportion of liver resections per age group and 30-day major morbidity and 30-day mortality were assessed. Results: In total, 6587 patients were included of whom 4023 (58.9%) were younger than 70, 2135 (32.4%) were septuagenarians and 429 (6.5%) were octogenarians. The proportion of septuagenarians increased during the study period (aOR:1.06, CI:1.02–1.09, p < 0.001). Thirty-day major morbidity was higher in septuagenarians (11%) and octogenarians (12%) compared to younger patients (9%, p = 0.049). Thirty-day mortality was higher in septuagenarians (4%) and octogenarians (4%) compared to younger patients (2%, p < 0.001). Cardiopulmonary complications occurred more frequently with higher age, liver-specific complications did not. Higher age was associated with higher 30-day morbidity and 30-day mortality in multivariable logistic regression. Conclusion : Thirty-day major morbidity and 30-day mortality are higher after liver resection in elderly patients, attributed mainly to non-surgical cardiopulmonary complications.